THE INFLUENCE OF GROUP INVESTIGATION COOPERATIVE LEARNING MODEL ON STUDENT LEARNING OUTCOMES IN WORK AND ENERGY MATERIALS IN CLASS X SMA NEGERI 12 MEDAN - Dian Limbong; Rahmatsyah Rahmatsyah (Program Studi Pendidikan Fisika FKIP Universitas Riau, 2017)
The purpose of this research is to know the student learning outcomes and student learning activities that use Cooperative Type Group Investigation model and conventional learning. The type of research is quasi experiment, and the sampling is done by simple random sampling. The instrument used is the cognitive learning outcomes test. From the data analysis for the experimental class learning outcomes, it results in an average of pretest 46,667 and posttest 73,714. The control class results in an average of pretest 40,381 and posttest 60,761. The result of data analysis using t-one test, when the result of t test is thitung = 4,056 while ttabel = 1,668, thitung> ttabel. Because then there is a significant difference, this shows there is the influence of the use of cooperative learning model of type group investigation of toward student learning outcomes content Work and Energy in class X Semester II SMA Negeri 12 Medan T.P 2016/2017.